10x-6=-3.5+10-2x

Simple and best practice solution for 10x-6=-3.5+10-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-6=-3.5+10-2x equation:



10x-6=-3.5+10-2x
We move all terms to the left:
10x-6-(-3.5+10-2x)=0
We add all the numbers together, and all the variables
10x-(-2x+6.5)-6=0
We get rid of parentheses
10x+2x-6.5-6=0
We add all the numbers together, and all the variables
12x-12.5=0
We move all terms containing x to the left, all other terms to the right
12x=12.5
x=12.5/12
x=1+0.5/12

See similar equations:

| -2(x-3)+4x-4=-14 | | -14x+8(x-3)+14=80 | | 3(3+2)=10x+6 | | t+37/7=8 | | 5(s-12)-24=3(s-12) | | 15x+7=15+15x | | 11+z/2=73 | | 9=0.6z | | m-2m-6=-12+2 | | 2x*6x=12x | | 10j+6=16 | | 4x+16=6(x-1) | | -35=b/6-38 | | 4x-8x-3=6-4x= | | 17x+9+21x-3+15x+15=180 | | 12+w=42 | | 46-v=250 | | 0,5+7x=12–2x | | 5x8=36+9x | | 1/3(x+2)=1/3x=2/3 | | 10x=30,x=3 | | 7+3c=64 | | 6(x-10)+2=4+2x | | 7x-38=70 | | .75x+80=6x+72 | | 2x2+4(x^2+3)-2=22 | | 5x+1=1-5x= | | 9v-9=45 | | -4(-2x=5)-5x=5=-24 | | F(0)=5x+2 | | 3x+57=20 | | .75+80=6x+72 |

Equations solver categories